Interactive Speech Based Assistive Game for Improving Spoken Language Skills in Children With Learning Disabilities - Dewan, Surbhi; Gautam, Sumanlata; Singh, Latika (Indian Journal of Computer Science, 2018)
Assistive technologies have proved to be one of the most powerful tools to aid people with learning disabilities to improve the quality of their lives. In the present study, an educational android application based on Hindi and English was developed to facilitate language learning in children with special needs. The main objective of this study was to provide a platform that is useful in enhancing the learning abilities and communication skills of children suffering from learning disability like autism, dyslexia, aphasia etc. The application was developed with three different complexity levels to cater to the needs of children with varied levels of severity of disorder. The proposed app based game was tested with a group of special kids and has reportedly shown positive results.